Techno-environmental assessment of a micro-cogeneration system based on natural gas for residential application (2018)
The advantage of using in-situ electricity generation facilities versus conventional generators, being evaluated from the environmental point of view, was studied. For this, an environmental analysis on the production of CO2 has been applied to two scenarios of electricity generation for a residential building in Medellin city (Colombia). First refers to La Sierra thermo-electric plant located in La Sierra, municipality of Puerto Nare, in the Antioquiashire, which is the most efficient plant in Colombian thermal generation. The second comparison scenario refers to the annual operation of a micro-cogeneration facility, which satisfies the building's hot water and electrical energy needs. Using the capabilities of the TRNSYS v17R energy simulation software and the emission equations available in the public domain, the comparative environmental analysis was performed between one and the other for the same load. The losses in electric transmission are assumed to be 10%. The analysis showed a difference of more than 50% in emissions generation, due mainly to the amount of fuel used, which for both cases, is natural gas. The environmental advantages in the use of in-situ generators include the decrease in transmission losses.